Narration Based On Corporate Social Responsibility (CSR) Advertisement: The Projection and Story - Natalia Widiasari (Institute of Research and Community Outreach - Petra Christian University, 2020)
Advertising plays an important role in narrating the social side of a company which is often referred to as Corporate Social Responsibility (CSR). Corporate social campaigns are often seen as dubious, however, audiences as individuals interpret advertisements based on their values and experiences. TBSI (The Body Shop Indonesia) advertisements were conceptualized and analyzed using narrative transportation. Interviews are conducted with nine informants from various backgrounds. The results of the study are described in themes, namely (1) insight, (2) the relationship between CSR messages and the participant's value system, and (3) narrative responses to CSR advertisements. The result of the study states that advertising does not necessarily make the value from a social issue to be embedded or instilled in someone. Narrative and commitment to these values depend on the individual, person by person.